HYBRID LEARNING DI STAIN MAJENE - Ahmad Ridhai Azis; Burhanuddin (PRODI PENDIDIKAN AGAMA ISLAM (PAI) SEKOLAH TINGGI AGAMA ISLAM NEGERI MAJENE, 2022)
This research aims to examine the effectiveness of Hybrid Learning at STAIN Majene in learning Indonesian Language. Hybrid Learning is developed for contemporary education. The learning problem in Covid-19 Pandemic Period are the environment and the learning media that have turned to virtual classes. The environment understood by students is a learning environment that presents lecturers in class, studying along with groups in the room. This contemporary education period present a learning with an independent concept and it is free to learn anywhere and anytime. The research approach was quantitative. The Research design was quasi-experimental. The research population was all the students who are in PAI 4 and PAI 6 semester I (odd) academic year 2020/2021. The data analysis techniques were used the SPSS24 application. The result of research showed that the learning outcomes of students in PAI 4 class following the learning process through Hybrid Learning as much as 89.70% succeed to achieve the average score of the minimum completeness criteria. The learning outcomes of students in PAI 6 as much as 91.68% succeed to achieve the average minimum completeness criteria. The use of Hybrid Learning effectively used in Indonesian language learning at STAIN Majene can be seen from the value of sig.(2-tailed)> 0.05 or 0.000>0.05, meaning that hypothesis 1 (H1) which states that Hybrid Learning is effectively used in learning at the Higher Lecturer level, especially in STAIN Majene. Keywords: effectiveness, hybrid learning, virtual class, Indonesian language